2016
DOI: 10.5539/jedp.v6n1p140
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of School Readiness and Poverty-Related Risk for 6th Grade Outcomes

Abstract: Low-income students are at increased risk for grade retention and suspension, which dampens their chances of high school graduation, college attendance, and future success. Drawing from a sample of 357 children and their families who participated in the Chicago School Readiness Project, we examine whether greater exposure to cumulative poverty-related risk from preschool through 5th grade is associated with greater risk of student retention and suspension in 6th grade. Logistic regression results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The majority of preschool directors agreed there are more, or a greater percentage of children who lack the basic skills for successful school transition when compared to a decade ago. Findings from this and other studies report an increase in the occurrence of developmental delay (Australian Early Development Census, 2018;Child Development Council, 2020;Dadson, Brown & Stagnitti, 2020;Pressler et al, 2016). Given the suggested link between developmental delay and inadequate school readiness, it can be assumed more children are commencing school less prepared.…”
Section: Discussionmentioning
confidence: 67%
“…The majority of preschool directors agreed there are more, or a greater percentage of children who lack the basic skills for successful school transition when compared to a decade ago. Findings from this and other studies report an increase in the occurrence of developmental delay (Australian Early Development Census, 2018;Child Development Council, 2020;Dadson, Brown & Stagnitti, 2020;Pressler et al, 2016). Given the suggested link between developmental delay and inadequate school readiness, it can be assumed more children are commencing school less prepared.…”
Section: Discussionmentioning
confidence: 67%
“…Few studies assessed socioeconomic gradients in effects within this review, a concern previously reported for school-based health interventions (Moore et al, 2015). Fade out of intervention effects over time may also be more of a concern amongst children from low SES backgrounds, and indicative of the higher number of stressors they experience and lower resources to adapt to them (Pressler et al, 2016). It is therefore important that intervention effects be considered based on child socioeconomic status, both over the short and long term.…”
Section: Discussionmentioning
confidence: 99%